Can current metrics characterise or differentiate between elite track and field athletes within the sprints, hurdles, high jump, long jump and triple jump? A systematic review - Turner, K. J.; Trowell, D.; Millett, E. L.; Bonacci, J.; Elvish, T. M.; Kremer, P.; Pickering, C.; Saunders, N. (Sports Medicine, 2025)
Background: High-performance sport programs aim to effectively identify talented athletes with the greatest potential for achieving podium success at benchmark events such as the World Championships or Olympic Games. However, not every talented athlete will go on to achieve success at the highest level, and the characteristics used to identify athletes are not well understood. Objective: The aim of this study was to systematically review the literature to understand parameters that may be associated with podium success at benchmark events in speed/power-based track and field events. Methods: A systematic search of articles was performed across Scopus, PubMed, EBSCOhost (Academic Search Complete and SPORTDiscus) and Web of Science based on Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines. Studies were eligible if they: (a) were published in English; (b) met the minimum performance criteria; (c) included track and field athletes in the 100-400 m sprint, 100/110 m hurdles, high jump, long jump or triple jump; and (d) examined biological or physical performance characteristics or determinants. Risk of bias was assessed using a 16-item checklist. Mean and standard deviations for sample characteristics and performance outcomes were analysed where possible. Articles based on competition data allowed for a comparison between medallists and non-medallists for each event group. Results: Forty-four articles were included in the systematic review. Of these 44 articles, 36 were competition analyses, five were field analyses (i.e. training) and three were laboratory analyses. Across the eight event groups investigated, ~ 509 athletes were evaluated with 323 athletes having individual competition data available for analyses. The key findings of reviewed studies were organised by event group. Medallists in the 100 m for both men and women achieved a greater peak velocity (men 0.46 m/s; women 0.22 m/s) and were better able to limit the deceleration phase. Compared with non-medallists in the 200 m, medallists were faster across the first 100 m for women (0.25 s) and second 50 m (0.10 s) and final 50 m for men (0.11 s). Medallists in the 400 m were faster in the final 150 m for both men (0.69 s) and women (0.58 s), compared with non-medallists. For both men and women in the sprint hurdles, the greatest differences between medallists and non-medallists emerged in the hurdle 9-10 unit time and run to the finish line time. Medallists in the men`s 400-m hurdles maintained a 13-step count between hurdles for one hurdle longer than non-medallists (who shifted to 14 steps), while finalists in the women`s event all followed a similar step pattern. The greatest differences in hurdle unit time between medallists and non-medallists emerged from hurdle five for women (medallists 0.18-0.22 s faster) and hurdle six for men (medallists 0.06-0.13 s faster). In the high jump, medallists for both men and women recorded a greater vertical velocity at take-off. Medallists also achieved a peak centre of mass height ~ 10 cm higher than their best bar clearance, while non medallists achieved a height ~ 5 cm higher. Medallists in the long jump for both men and women achieved a greater horizontal velocity at touchdown prior to take-off (men 0.41 m/s; women 0.30 m/s) than non-medallists. Male medallists also achieved a greater horizontal velocity at take-off (0.29 m/s) while female medallists achieved a greater vertical velocity (0.23 m/s). Male triple jump medallists were jump dominant while non medallists were hop dominant and there was no difference for women. For both men and women, medallists maintained a greater horizontal velocity across the triple jump phases. Conclusions: Across the eight event groups examined, various characteristics that may be associated with benchmark event podium success were identified. However, their ability to reliably differentiate between medal winners and non-medal winners remains inconclusive. While these characteristics may not be able to definitively identify podium success, they can be used to inform performance testing or areas for development.